Catalytic Application of Tactically Aligned Cd(II)‐Based Luminescent 3D‐Supramolecular Networks . Issue 24 (27th June 2019) - Rajak, Richa; Mohammad, Akbar; Chandra, Prakash; Mobin, Shaikh M.
Abstract: A new Cd(II) based coordination polymers {[Cd(Azopy)(H2 O)4 ]⋅(NDC)} n (1 ) has been designed and synthesized by using 4, 4′‐Azopyridine (Azopy), and 2, 6‐Naphthalene dicarboxylic acid (NDC) as a linker at ambient condition. The bulk purity of the 1 was analysed by powder X‐ray diffraction (PXRD) analysis, infrared spectroscopy and further confirmed by single crystal X‐ray studies. The crystal structure of 1 revealed a polythreading feature where each 2, 6‐naphthalene dicarboxylate unit are trapped between two one‐dimensional (1D) chain of [Cd(Azopy)(H2 O)4 ]∞ via strong hydrogen bonding interactions. The hydrogen bonding and π⋅⋅⋅π stacking interactions of 1 play a crucial role in the formation of the infinite 3D‐layered supramolecular network. Furthermore, the reduction of nitro‐aromatics to their corresponding amines was performed using green hydrogen source such as D‐glucose in H2 O solvent at room temperature. Additionally, the dye adsorption studies revealed that 1 can adsorb Congo Red (CR) dye in a very short span of time. The kinetic study result reveals that the adsorption of CR for 1 is fitted well (R 2 =0.996) with a pseudo‐second‐order kinetic model. Moreover, photoluminescence of 1 shows emission in the blue region with λmax at 395 nm and 408 nm at room temperature in the solid state. 1 shows multi‐facet behaviour such as facile synthesis, luminescent nature in solids‐state, emerged as a heterogeneous dye‐adsorbent and catalyst which makes it easy to scaled‐up. Abstract : A Simple, water stable and reusable slow‐diffusion driven supramolecular self‐assembled Cd(II) 3D‐network (1) having polythreding features was identified with multi‐applications as a catalyst for eco‐friendly reduction of nitroarenes using D‐glucose and water under at ambient conditions and dye adsorbent for water remediation. 1 also shows emission in the blue region with λmax at 395 nm and 408 nm at room temperature in the solid state.